The Effectiveness of Memrise as a Vocabulary Learning Tool - Aprizal, Agung Dwi; Wachyudi, Kelik (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research examines the effectiveness of Memrise, a mobile vocabulary learning app, in enhancing vocabulary retention for language learners. In the context of digital advancements reshaping education, Memrise's gamified approach provides an engaging platform for vocabulary mastery. Drawing on cognitive theories, including Cognitive Load Theory and Spaced Repetition, the study analyzes how Memrise utilizes these principles to bolster vocabulary retention. Through a literature review of 20 sources, common themes, patterns, discrepancies, and future research suggestions are identified. Findings underscore Memrise's potential in vocabulary learning, with themes including mobile app preferences, gamification, motivation, autonomy, and technical considerations. While nuances exist, the overall consensus supports Memrise's positive impact on language education. The study underscores the need for further research to explore wider contexts, replication, and addressing technical aspects. Ultimately, Memrise demonstrates promise in improving vocabulary acquisition through its gamified interface, contributing to the evolving landscape of language education.